Late Oligocene-Miocene intra-continental mountain building of the Harke Mountains, southern Chinese Tian Shan: Evidence from detrital AFT and AHe analysis. (15th April 2020) - Jia, Yingying; Sun, Jimin; Lü, Lixing; Pang, Jianzhang; Wang, Ying
Graphical abstract: Highlights: The intra-continental deformation commenced at 26–23 Ma in Harke Mountain. The exhumation of Harke Mountains intensified between 10 and 6 Ma. The Late Miocene exhumation is probably a regional tectonic event of the Tian Shan. Abstract: As the largest intra-continental mountain belt in Central Asia, the Tian Shan mountain range underwent a diachronous uplift history in different regions. The present crustal shortening rate of this mountain range is also characterized by an along-strike variation and decreases from west to east. The Harke Mountains, located in the middle part of the southern Tian Shan, accommodate a relatively lower crustal shortening rate but host the highest topography of this mountain range. This study aims to restore the Cenozoic mountain building history of the Harke Mountains. Detrital AFT and AHe analyses were conducted for Paleocene-Pliocene sediments and modern moraines in the Kuqa depression. An abrupt increase in the lag time of the detrital AFT young age components at 26–23 Ma indicates that the uplift of the southern Tian Shan initiated in the Late Oligocene-Early Miocene, which is consistent with the regional tectonic activation of the Tian Shan mountain range. In the Late Miocene, the basement of the Harke Mountains underwent rapid exhumation from 10 to 6 Ma. Comparing our result with previously published tectonic data, we infer that the intense exhumation in our study area corresponds to the intensified deformation of the whole Tian Shan mountain range in the Late Miocene, which was probably driven by the accelerated convergence between the Tarim and Tian Shan.